Vpliv delovnopravnega, državljanskega in družinskopravnega statusa na neenako obravnavo v zdravstvenem zavarovanju - Rajgelj, Barbara (Zdravstveno varstvo, 2012)
Background: Right to health care is a human right, which should - because of its universal status - belong to an individual regardless of his or her personal circumstances. In the legislative process different systems provide different criteria for accessibility and funding of this right. In doing so, one can observe how respective social priorities affect inclusion and exclusion of beneficiaries of health care on the ground of their legal status. Methods: This article is based on analysis and interpretation of primary and secondary sources, particularly national and international legal acts regarding constitutional right to health care, health care and health insurance, employment and family relations and the law of aliens. Results: As the enjoyment of the right of health insurance depends on an individual's labour, citizenship and family status, the users of health care are treated unequally. The legislation is based on the assumption that work is normally performed in the form of an employment relationship. In modern times, however, atypical forms of work are on the rise and therefore health insurance rights are thus differently available to different persons of the same actual but different legal status. The rights of persons, who are not insured on the basis of a labour status, are subsidiary tied to family relations and their enforcement thus also depends on whether the person is married, living in a de facto union, same-sex partnership or is single. Nevertheless, right to health insurance is affected also by citizenship and different kinds of foreignness. Conclusion: Despite objective of universal health insurance coverage of all inhabitants, a growing number of inhabitants remain without basic health insurance. The most vulnerable are foreigners without permanent residence, self-employed persons and their family members, registered and unregistered same-sex partners, single persons and children in the reorganized families.
Keywords: Človekove pravice; Health insurance; Human rights; Legal sources; Medical care; Pravni viri; Zdravstveno varstvo; Zdravstveno zavarovanje